EDUCATION IN THE CHILDREN’S AND YOUNG PEOPLE’S HEALTH SAVING: EUROPEAN RETROSPECTIV, BECOMING IN THE POLAND LANDS - Slyvka, Larysa (Mountain School of Ukrainian Carpaty, 2020)
The article presents domestic researchers, who researched the retrospective of formation of pedagogical models of health saving of growing personality : V. Bobrycka, Y. Boychuk, E. Bulych, I. Muravov, O. Vashchenko, S. Verhratski, P. Zabludovski, I. Dacenko, P. Djurynski, T. Yermakova, V. Yefimova, N. Mogaricheva, L. Jovnirenko, S, Kyrylenko, V. Kuksa, L. Sushchenko, S. Fil, O. Hudoliy, G. Malka, L. Sheremet and polish researchers L. Vynnychuk, B. Galonzka, M. Demel, T. Drabchyk, P. Mazur, E. Pyasecki and others. Summarizing the content of the intelligence of the mentioned authors showed that the most studied in the context of the topic of the article is the «ancient» period of human civilization and the Renaissance. The article describes Jan Amos Komensky’s didactic aspects of optimization of health care of children and youth, highlights the health-oriented dimensiom of John Locke’s gentleman’s upbringing, expressed Jean-Jacques Rousseau’s health-saving pedagogical program. Claude Adrian Helvetius’ views on physical education as a means of shaping the health of a growing personality are represented. The article presents the Johann Henry Pestalozzi’s health-saving practices. The vision of the health-saving function of physical education by Johann Christoph Friedrich Guts-Muts is updated. Giovanni Bosco and Herbert Spencer’s views on physical component in health-saving activiyies announced. The article presents the humanistic concepts of education and upbringing of Ellen Carolina Sophia Kay, Wilhelm August Lai, Georg Kerschensteiner and Maria Montessori.